Análisis de la cooperación internacional del ACNUR para las personas solicitantes y refugiadas en el Ecuador, 2012-2016 - Arellano Chimbolema, Simón Bolívar (2017)
The present research analyzes the International Cooperation of UNHCR for applicants and refugees in Ecuador between the period 2012 - 2016. This study is based on the main international instruments for the granting of refugee status, norms such as Decree 1182, Constitution of 2008, Judgment No. 002-14-SIN.CC and the LOMH in the matter. In addition, regarding the role of UNHCR in Ecuador, how its funds have contributed to the applicants and refugees, operating through two organizations HIAS and Asylum Accesss, which work with UNHCR funds in an articulated way. In this sense, the research takes as reference the group of applicants and refugees from Colombia, Cuba, Peru and Afghanistan that are in Ecuador under the figure of international protection. In addition, analyzes the international agencies UNHCR, Asylum Access and HIAS assistance's distribution in the country and which citizens benefit more and why.